Putative Novel Genotype of Avian Hepatitis E Virus, Hungary, 2010 - Ivanics, Eva; Dan, Adam; Banyai, Krisztian; Toth, Adam Gyorgy; Szentpali-Gavaller, Katalin; Glavits, Robert (Emerging infectious diseases, 2012)
To explore the genetic diversity of avian hepatitis E virus strains, we characterized the near-complete genome of a strain detected in 2010 in Hungary, uncovering moderate genome sequence similarity with reference strains. Public health implications related to consumption of eggs or meat contaminated by avian hepatitis E virus, or to poultry handling, require thorough investigation.